Electromagnetic Field in Advancing Science and Technology - Song, Hai-Zhi; Ho Yeap, Kim; Wan Ching Goh, Magdalene (IntechOpen, 2023)
As a fundamental aspect of science and technology, the electromagnetic field has infiltrated most human activities. This book reviews recent achievements in electromagnetic field theory, in the scientific research driven by the electromagnetic field, and in the application of the electromagnetic field in advanced technology. Theoretical aspects of the electromagnetic field are examined in detail and new interpretations of the basic interactions related to magnetic fields are proposed. Among the scientific research topics reviewed, new understandings are achieved of long-distance wireless power transfer, nerve impulses, and electromagnetic diagnosis mechanisms. A new concept of the electric field at the verge of discharge is applied to the electric fields produced by any distribution or structure of electric charges in clouds. The detailed relationship between materials and microwave electromagnetic fields is described in order to achieve fine control of the chemical reaction field in materials under microwave irradiation. Electromagnetic power consumption in microelectronic devices is carefully analysed, enabling power saving in CMOS/FinFET circuits. The effective use of 2D materials in newly developed electronic, electromagnetic resistive switching devices is investigated.